Handschrift im Druck (ca. 1500-1800) Annotieren, Korrigieren, Weiterschreiben - Brockstieger, Sylvia; Hirt, Rebecca (Materiale Textkulturen, 2023)
This edited volume examines the forms and functions of the interaction between hand writing and print culture in the period ca. 1500 to 1800. Handwritten interventions into printed books interrupt the text fixed in print by commenting on it, correcting it, or expanding it. They point to changing contexts of use, the flexibilization of supposedly static concepts of authorship, and the dynamics of correction processes.